Notes sobre els autors mallorquins contemporanis - Nadal, Antoni (Caplletra. Revista Internacional de Filologia, 2015)
A study of the activity and dramatic production in Majorca from the immediate post-war to the present. Starting from the regional theatre, with its exclusively commercial vocation, the author goes on to analyze the attempts of providing theatrical plays with solid cultural bases, by the dignification of the dramatic text and the synchronization with European theatrical trends, as well as by employing the most experimental formulae.